Food structure : its creation and evaluation : Symposium : 44th Easter school in agricultural science : Papers - Mitchell, J. R., Ph. D. (Woodhead Publishing Ltd, 1987)
The book considers fundamental concepts and discussed dispersed food systems such as gels, emulsions and foams and chemical properties of food polymers.